Asymmetric electric field distribution enhanced hierarchical metamaterials for radar-infrared compatible camouflage. (20th May 2023) - Zhang, Tuo; Duan, Yuping; Liu, Jiangyong; Lei, Hao; Sun, Jingxuan; Pang, Huifang; Huang, Lingxi
Highlights: Square frustum metastructure composites are fabricated and optimized based on genetic algorithms. The hierarchical strategy and asymmetric infrared unit create a nonuniform distribution of the electromagnetic field in the near local field, contributing to broadening the absorption bandwidth. The designed metamaterial with a subwavelength thickness of 0.049 λ max achieves excellent radar-infrared compatible camouflage that microwave absorption bandwidth is 12.2 GHz and infrared emissivity is 0.29. Abstract: Metamaterials are widely used in electromagnetic radiation and camouflage for their flexible wavefront manipulation and polarization over a broad spectrum ranging from microwaves to optics. However, multispectral compatible camouflage faces significant challenges due to tremendous scale differences of unit cells and desired radiative properties in various spectral regimes. This study assembles a micron-scale infrared emitter, a millimeter-scale microwave absorber, and a metal reflector to propose a hierarchical metamaterial that reduces microwave scattering and reflects low-infrared waves. As a proof of concept, laser etching micro-manufactures an upper infrared shielding layer with a periodic metal pattern. At the same time, bottom square frustum metastructure composites are fabricated and optimized based on genetic algorithms. Under the normal incidence transverse electromagnetic wave with a 90° azimuth angle, the hierarchical strategy and infrared unit create an asymmetric electric field distribution of local near-field coupling, which is conducive to generating additional resonance for broadening the absorption bandwidth. Experiments verify the multispectral camouflage, which shows a high absorption efficiency of more than 90%, ranging from 3.6 to 6.2 and from 8.4 to 18 GHz with a total thickness of 4.05 mm (0.049 λ max ). Due to the non-reflection of surrounding thermal signals in the infrared 2-22 μm region, low-infrared emissivity (0.29) metamaterials can adapt to various thermal backgrounds. This methodology can provide a novel route for fabricating multispectral camouflage devices.